Custom 3D-printed Total Talar Prostheses Restore Normal Joint Anatomy Throughout the Hindfoot. Issue 3 (14th September 2018) - Tracey, Joseph; Arora, Danny; Parekh, Selene
Category: Hindfoot Introduction/Purpose: Third generation total talar prostheses (TTP) are viable options for talar avascular necrosis (AVN) in the absence of neighboring joint pathology. The use of modern three-dimensional (3D) printing allows for the production of custom implants that exactly mimic the patient's anatomy. The aim of this study is to determine the accuracy of 3D printing in reproducing a synthetic talus, and in doing so, restoring more normal anatomic relationships. We hypothesize that this mode of replication will restore and maintain normal radiographic alignment of the ankle, subtalar, and forefoot joints in the setting of talar AVN. Methods: A retrospective analysis was performed on all patients undergoing TTP implantation for the treatment of talar AVN between 2016 and 2017. Pertinent demographic and operative factors were recorded. Radiographic measurements were taken pre- and post-operatively to determine native talar dimensions, TTP implant dimensions, and the corresponding radiographic alignment about the forefoot, hindfoot, and ankle. Results: Fourteen patients, treated for AVN between 2016-2017, were identified in our cohort. Talar arc length and width were not found to be significantly changed, however talar height was significantly increased with use of TTP. Five alignment dimensions were measured (tibiotalar alignment, talar tilt angle, Boehler's angle, talar declination angle, and Meary's Angle), of which, only talar tilt angle was significantly changed. Instances of Meary's angle correction were observed in cavus and planus foot deformity. Conclusion: This study represents the largest case series of TTP performed in the United States, and is the first to investigate the 3D printed TTP. As a proof-of-concept, 3D printed TTP was successful in restoring talar height and talar tilt in the setting of AVN. Additionally, the procedure maintained normal alignment in non-pathologic joints. Total talar prosthesis, based on our cohort, is a viable option to restore more normal anatomic alignment.